Bacterial Engulfment Mechanism Is Strongly Conserved in Evolution Between Earthworm and Human Immune Cells - Kokhanyuk, Bohdana; Bodó, Kornélia; Sétáló Jr, György; Németh, Péter; Engelmann, Péter (Frontiers in Immunology, 2021)
Invertebrates, including earthworms, are applied to study the evolutionarily conserved cellular immune processes. Earthworm immunocytes (so-called coelomocytes) are functionally similar to vertebrate myeloid cells and form the first line of defense against invading pathogens. Hereby, we compared the engulfment mechanisms of THP-1 human monocytic cells, differentiated THP-1 (macrophage-like) cells, and Eisenia andrei coelomocytes towards Escherichia coli and Staphylococcus aureus bacteria applying various endocytosis inhibitors (amantadine, 5-(N-ethyl-N-isopropyl) amiloride, colchicine, cytochalasin B, cytochalasin D, methyl-ß-cyclodextrin, and nystatin). Subsequently, we investigated the mRNA expressions of immune receptor-related molecules (TLR, MyD88, BPI) and the colocalization of lysosomes with engulfed bacteria following uptake inhibition in every cell type. Actin depolymerization by cytochalasin B and D has strongly inhibited the endocytosis of both bacterial strains in the studied cell types, suggesting the conserved role of actin-dependent phagocytosis. Decreased numbers of colocalized lysosomes/bacteria supported these findings. In THP-1 cells TLR expression was increased upon cytochalasin D pretreatment, while this inhibitor caused a dropped LBP/BPI expression in differentiated THP-1 cells and coelomocytes. The obtained data reveal further insights into the evolution of phagocytes in eukaryotes. Earthworm and human phagocytes possess analogous mechanisms for bacterial internalization.